(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the current state of state-confessional relations in Kazakhstan. It shows how in the secular, poly-confessional Kazakhstan society the problems of religion are being solved, the positive role of Islam and Orthodoxy in preserving the accord, peace between different religions is revealed, legislative acts in the field of religion and religious associations are analyzed. The main provisions and principles of the Kazakhstan model of interconfessional consent, the role of dialogue, tolerance in its formation. Attention is also paid to holding congresses of leaders of world and traditional religions, thanks to which Kazakhstan is deservedly recognized by the world community as an interactive platform in solving religious problems, interconfessional relations. The problems of strengthening the security and stability of society, the consolidation of various forces, including religious ones, are key moments in the state-confessional policy of our country. Key words: state-confessional relations, religion, religious associations, confessional space, secular state, freedom of religion, tolerance, consent, tolerance, dialogue.